50th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2012
DOI: 10.2514/6.2012-623
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Aero-Optical and Mechanical Jitter for Flat Window Turrets

Abstract: Simultaneous local jitter, 2-D wavefronts and accelerometer measurements were performed in the flow over a flat-window turret at Mach numbers between 0.3 and 0.4 along a centerplane with a viewing angle varying between 90 and 118 degrees. Both local and global jitter imposed on a small-and large-aperture laser beams were measured using positionsensing devices and a high-speed 2-D wavefront sensor. A linear stochastic estimation technique was applied to separate the mechanically-related component of the jitter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 7 publications
(14 reference statements)
0
27
0
Order By: Relevance
“…The relation between the global and the local tilt was derived by DeLucca et al (2012) and it was shown that the removal of the global tilt works as a high-pass filter on the local deflection angle, with the transfer function, G A (z) = [3 sin(πz) − 3πz cos(πz)](Colour online) (a) Streamwise deflection-angle amplitude spectra computed from 1-D wavefront data for different apertures, compared with the Malley probe deflection-angle amplitude spectrum. (b) Streamwise deflection-angle amplitude spectra computed from 1-D wavefront data for different apertures, corrected for aperture effects, the corrected Malley probe deflection-angle amplitude spectrum and the empirical fit, given by (4.2).…”
mentioning
confidence: 99%
“…The relation between the global and the local tilt was derived by DeLucca et al (2012) and it was shown that the removal of the global tilt works as a high-pass filter on the local deflection angle, with the transfer function, G A (z) = [3 sin(πz) − 3πz cos(πz)](Colour online) (a) Streamwise deflection-angle amplitude spectra computed from 1-D wavefront data for different apertures, compared with the Malley probe deflection-angle amplitude spectrum. (b) Streamwise deflection-angle amplitude spectra computed from 1-D wavefront data for different apertures, corrected for aperture effects, the corrected Malley probe deflection-angle amplitude spectrum and the empirical fit, given by (4.2).…”
mentioning
confidence: 99%
“…Recent careful comparisons between timeresolved 2-D wavefront measurements and 1-D Malley probe wavefront measurements have shown that there is significant low-frequency corruption in the Malley probe spectra from various sources [13]. It was shown in [13] that less-corrupted experimental measurements of the low-frequency (below-peak) deflection angle spectra can be obtained from time-resolved 2-D wavefront measurements, once correction for a finite-aperture size from [17] has been applied. This correction is necessary since wavefront tip/tilt removal has been shown to act as a high-pass filter…”
Section: One-dimensional Wavefront Resultsmentioning
confidence: 99%
“…, where = [3 sin( ) − 3 cos( )] /( ) 3 , and = 1.2( / ) [17]. A comparison of Malley-Probe spectra and aperture-corrected wavefront spectra is shown in Figure 6.…”
Section: One-dimensional Wavefront Resultsmentioning
confidence: 99%
“…While the turret vibrational response depends on an internal structure, an unsteady pressure field depends only on the turret geometry Gordeyev at al AIAA-2013-XXXX 2 American Institute of Aeronautics and Astronautics and the incoming Mach number. In addition, unsteady pressure fluctuations on the surface of the turret are directly related to the turbulent structures, causing aero-optical global jitter and higher-order aberrations [10].…”
Section: Introductionmentioning
confidence: 99%